2017
DOI: 10.1093/molbev/msx086
|View full text |Cite
|
Sign up to set email alerts
|

Frozen in Time: The History of Proteins

Abstract: The ribosome is imprinted with a detailed molecular chronology of the origins and early evolution of proteins. Here we show that when arranged by evolutionary phase of ribosomal evolution, ribosomal protein (rProtein) segments reveal an atomic level history of protein folding. The data support a model in which aboriginal oligomers evolved into globular proteins in a hierarchical step-wise process. Complexity of assembly and folding of polypeptide increased incrementally in concert with expansion of rRNA. (i) S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
76
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(92 citation statements)
references
References 38 publications
(60 reference statements)
9
76
0
Order By: Relevance
“…Characteristics of the operational code are consistent with recent suggestions that protein structures evolved coordinately with the alphabet size and that the evolution of the genetic code also traces the discovery of protein folding rules (5). Correlations between secondary and tertiary structures of ribosomal proteins and the estimated order of rRNA additions provoked a similar hypothesis from an entirely different direction (29). Those authors postulated staged protein evolution, earlier stages marked initially by the absence of secondary structures, followed by the presence of β-, then α-structures, and then only after a prolonged development of secondary structures, by the emergence of tertiary structures.…”
Section: Conclusion Future Directionssupporting
confidence: 82%
“…Characteristics of the operational code are consistent with recent suggestions that protein structures evolved coordinately with the alphabet size and that the evolution of the genetic code also traces the discovery of protein folding rules (5). Correlations between secondary and tertiary structures of ribosomal proteins and the estimated order of rRNA additions provoked a similar hypothesis from an entirely different direction (29). Those authors postulated staged protein evolution, earlier stages marked initially by the absence of secondary structures, followed by the presence of β-, then α-structures, and then only after a prolonged development of secondary structures, by the emergence of tertiary structures.…”
Section: Conclusion Future Directionssupporting
confidence: 82%
“…Characteristics of the operational code are consistent with recent suggestions that protein structures evolved coordinately with the alphabet size and that the evolution of the genetic code also traces the discovery of protein folding rules (4). Correlations between secondary and tertiary structures of ribosomal proteins and the estimated order of rRNA additions provoked a similar hypothesis from an entirely different direction (28). Those authors postulated staged protein evolution, earlier stages marked initially by the absence of secondary structures, followed by the presence of β-, then α-structures, and then only after a prolonged development of secondary structures, by the emergence of tertiary structures.…”
Section: Conclusion Future Directionssupporting
confidence: 82%
“…Second, while binding and hydrolysis of phosphorylated nucleosides (NTPs) is the hallmark of modern P-loop NTPases, we have uniquely observed that the P-loop prototypes not only interact with NTPs, but also and foremost, avidly bind RNA and ssDNA. This raises the tantalizing possibility that early P-loop proteins emerged in a context of polynucleotide binding, and RNA in particular (57). Although some potential to hydrolyze NTP might be attributed to our P-loop prototypes, the far more efficient enzymatic NTPase functions we see today were likely acquired at a later stage when higher sequence and structural complexity evolved, including the acquisition of a magnesium-binding site and an activesite cavity.…”
Section: Discussionmentioning
confidence: 91%